Hadith #3142 - Sunan al-Nasa'i - Amr bin 'Uthman bin Sa'id bin Kahtir عمرو بن عثمان بن سعيد بن كثير; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي; Sharhbayl bin al-Samat; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري (Sunan al-Nasa'i)
“A Bedouin came to the Messenger of Allah (ﷺ) and said: ‘A man fights for fame, or he fights for the spoils of war, or he fights to show off. Who is the one who is fighting in the cause of Allah?’ He said: ‘The one who fights so that the word of Allah will be supreme is the one who is fighting in the cause of Allah, the Mighty and Sublime.'”
Grade:

Hadith #2758 - Sunan Abi Dawud - Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري (Sunan Abi Dawud)
The Quraysh sent me to the Messenger of Allah (ﷺ), and when I saw the Messenger of Allah (ﷺ), Islam was cast into my heart, so I said: Messenger of Allah, I swear by Allah, I shall never return to them. The Messenger of Allah (ﷺ) replied: I do not break a covenant or imprison messengers, but return, and if you feel the same as you do just now, come back. So I went away, and then came to the Prophet (ﷺ) and accepted Islam. The narrator Bukair said: He informed me that Abu Rafi’ was a Co
Grade: Sahih

Hadith #3836 - Sunan Abi Dawud - al-Walid bin Mazyad الوليد بن مزيد; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to eat melon with fresh dates, and he used to say: The heat of the one is broken by the coolness of the other, and the coolness of the one by the heat of the other.
Grade: Sahih

Hadith #3965 - Sunan Abi Dawud - Abd al-Whab bin Njd'h عبد الوهاب بن نجدة; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي; Sharhbayl bin al-Samat; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري (Sunan Abi Dawud)
Along with the Messenger of Allah (ﷺ) we besieged the palace of at-Ta’if. The narrator, Mutadh, said: I heard my father (sometimes) say: “Palace of at-Ta’if,” and (sometimes) “Fort of at-Ta’if,” which are the same. I heard the Messenger of Allah (ﷺ) say: he who causes an arrow to hit its mark in Allah’s cause will have it counted as a degree for him (in Paradise). He then transmitted the rest of the tradition. I heard the Messenger of Allah (ﷺ) say: If a Muslim man emancipa
Grade: Sahih

Hadith #616 - Jami' al-Tirmidhi - Abu Umama al-Bahili; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Jami' al-Tirmidhi)
“I heard Abu Umamah saying: I heard the Messenger of Allah giving a Khutbah during the Farewell Hajj, and he said: ‘Have Taqwa of your Lord, and pray your five (prayers), and fast your month, and pay the Zakat on your wealth, and obey thosewho are in charge of you, you will enter the Paradise of your Lord.'” He said: “I said to Abu Umamah: ‘How old were you when you heard this Hadith (from the Messenger of Allah)?’ He said: ‘I heard it when I was thirty years old.'”
Grade:

Hadith #1495 - Jami' al-Tirmidhi - Abdul Quddus bin al-Hajjaj al-Khulani عبد القدوس بن الحجاج الخولاني; Abu Umama bin Sahl; Salmah bin Shbyb سلمة بن شبيب; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري (Jami' al-Tirmidhi)
That the Messenger of Allah (ﷺ) said: “Whoever acquires a dog – with the exception of a dog to guard livestock, a hunting dog, or a farm dog – each day a Qirat is deducted from his reward.”
Grade:

Hadith #1546 - Jami' al-Tirmidhi - Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري (Jami' al-Tirmidhi)
“I said: ‘O Messenger of Allah! My sister vowed that she would walk to the House barefoot and without Khimar (covering).’ The Prophet (ﷺ) said: ‘Verily Allah will not do anything with the misery of your sister. She should ride, and cover, and fast three days.'”
Grade:

Hadith #2290 - Jami' al-Tirmidhi - Abbas bin Muhammad bin Hatm عباس بن محمد بن حاتم; Abu Umama al-Bahili; Huraiz bin 'Uthman bin Jabir حريز بن عثمان بن جبر الرحبي; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري; Yahya bin Abi Bkyr يحيى بن أبي بكير واسمه نسر (Jami' al-Tirmidhi)
“In the end of time, the dreams of a believer will hardly ever fail to come true, and the most truthful of them in dreams will be the truest in speech among them. And dreams are three types: The good dreams wihich is glad tidings from Allah, dreams about something that has happened to the man himself, and dreams in which the Shaitan frightens someone. So when one of you sees what he dislikes, then he should get up and perform Salat.” Abu Hurairah said: “I like fetters and dislikes, the
Grade:

Hadith #2535 - Jami' al-Tirmidhi - Abdullah bin Mubarak عبد الله بن المبارك; Abdur Rahman bin Yazid bin Jabir عبد الرحمن بن يزيد بن جابر الأزدي; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Jami' al-Tirmidhi)
“The believer shall be given in paradise such and such strength in intercourse .” it was said: “O Messenger of Allah! And will he able to do that?” He said: “He will be given the strength of a hundred.”
Grade:

Hadith #2881 - Sunan Ibn Majah - Abu Umama al-Bahili; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري; Ubaidullah bin Yusuf عبيد الله بن يوسف الجبيري (Sunan Ibn Majah)
“I asked Abu Ayyub Al- Ansari: ‘How were sacrifices offered among you at the time of the Messenger of Allah (ﷺ)?’ He said: ‘At the time of the Prophet (ﷺ), a man would sacrifice a sheep on behalf of himself and the members of his household, and they would eat some of it and give some to others. Then people started to compete and it because as you see (nowadays).’”
Grade:

Hadith #3248 - Sunan Ibn Majah - Abu Umama al-Bahili; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري (Sunan Ibn Majah)
It as narrated from Abu Bakr bin Muhammad that Khalidah bint Anas, the mother of Banu Hazm As-Sa’idiyyah, came to the Prophet (ﷺ) and recited a Ruqyah to him, and he told her to use it.
Grade:

Hadith #3457 - Sunan Ibn Majah - Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Sdqh bin Khalid al-Amwy صدقة بن خالد الأموي; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري (Sunan Ibn Majah)
“The Messenger of Allah(ﷺ) found me sleeping in the masjid on my stomach. He nudged me with his foot and said: ‘Why are you sleeping like this? This is a kind of sleep that Allah dislikes,’ or ‘that Allah hates.'”
Grade:

Hadith #3781 - Sunan Ibn Majah - Abu Umama bin Sahl; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري (Sunan Ibn Majah)
“The Hour will not begin until the Euphrates uncovers a mountain of gold and people fight over it, and out of every ten, nine will be killed.’”
Grade:

Hadith #3847 - Sunan Ibn Majah - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaym bin 'Amir al-Kula'i al-Khaba'ri سليم بن عامر الكلاعي الخبائري; Ubaid bin Sa'id bin Aban bin Sa'id عبيد بن سعيد بن أبان بن سعيد; Yazid bin Khumayr al-Rahbi يزيد بن خمير (Sunan Ibn Majah)
“I was riding with the Messenger of Allah (ﷺ) when he came across a dead lamb that had been thrown out.’ He said: ‘Don’t you think that this is worthless to its owners?’ It was said: ‘O Messenger of Allah, it is because it is worthless that they have thrown it out, – or words to that effect. He said: ‘By the One in Whose Hand is my soul, this world is more worthless to Allah than this is to its owners.’”
Grade: